Features of change in the process of wear of tribological properties of metal surfaces of fortified by the action of electric pulses - Бобер, М.В.; Варченко, В.Т.; Аврамчук, С.К.; Волкогон, В.М. (Problems of Tribology, 2014)
Tribological properties of fortified are studied by the action of impulsive electric pulses and unfortified standards of rails after rolling at the layer removal of material of designing them wear in the process of exploitation. It is shown that strengthening of rails by forming on their surface of irregular microrelief provides the increase of tribological descriptions of material the action of electric pulses during all process of wear.